The Fundamental Marxian Theorem: A Reply to Samuelson - Morishima, Michio (Journal of Economic Literature, 1974)
and, therefore, T* equals the value of the subsistence commodity-bundle, AB, that is the labor-time socially necessary for producing B by the techniques (a, a.) actually prevailing in the economy. It is important to emphasize that there is no element of competitive arbitrage in (4). It is no more than the equation for calculation of the quantities of labor socially necessary for producing goods.